Investigation of fuel sloshing in an aircraft wing fuel tank using ANN and CFD - Kayahan, Kerem (Graduate School, 2025)
In civil and military aviation, it is crucial to develop designs that adhere to specific requirements based on their intended use. This process involves thoroughly completing and documenting flight tests, as well as securing airworthiness certificates for the relevant aerial domain. Thus, aircraft and their associated systems, comprising subsystems and equipment that operate in conjunction, undergo a variety of performance evaluations. This approach ensures that all systems function seamlessly and achieve optimal performance levels, as evidenced by numerical data and recognized international documentation. Fuel systems, essential for flight operations, encompass all stages, from refueling the tanks to supplying fuel to the engine that generates thrust for the aircraft. These systems comprise several components that interact with other systems, including hydraulic, avionics, structural, and landing gear systems, and must align with the specific requirements imposed by each of these interrelated systems. The applicable requirements dictate that considerations such as structural integrity, thermal dissipation limits, compatibility with electronic equipment, and overall equipment weight must be addressed concurrently. The primary subsystems within the aviation fuel system are categorized under several critical headings, including hydraulic cooling, engine feeding, indication, and storage. Among these subsystems, the storage component significantly influences flight mechanics and has a considerable impact on overall weight. Given the specified requirements for the flight range, the stored fuel must adhere to a maximum mass limit, which means that a substantial fluid mass must be integrated into the aircraft's flight mechanics. Since this mass is fluid, its response to maneuvers manifests as sloshing mechanics. Consequently, the aircraft's center of gravity tends to shift as sloshing persists. The movement of the fuel and its effects on the center of gravity can be managed through design considerations in the storage area. Tanks that result in variations of the center of gravity due to fuel sloshing are typically incorporated into the aircraft's wings, fuselage, and, in some cases, external fuel tanks. However, as general-purpose primary training aircraft are the focus of this thesis study, no fuselage or external tanks are considered; the research is thus limited to the fuel stored within the wings. The wing tanks of the aircraft are designed symmetrically, with their placement mirrored across both wings. Under ideal conditions, the engine supply is also maintained to be as symmetrical as possible. However, since ideal flight conditions are nearly never achieved in practice, this symmetry is frequently disrupted by external factors and flight maneuvers. As a result, the movement of fuel within the wing can cause the center of gravity to deviate from the intended position due to gravitational effects. Various design features are integrated into the structural components of the wing to mitigate this issue. These features serve two primary purposes: firstly, to minimize the rate at which fuel deviates from its original position during maneuvers, and secondly, to facilitate the rapid return of the fuel to its initial position once the maneuver is completed. The qualitative and quantitative aspects of these design features are subject to constraints related to manufacturing feasibility, weight requirements, and structural integrity. The design elements discussed in this thesis focus on practical applications in the industry rather than purely theoretical approaches, and they provide examples that can be implemented in many primary training aircraft. In this context, the design details studied are discussed in the structural parts of the rib, which form the structure inside the wing tank and divide the tank into subsections. These ribs, called baffles, contain cutout holes that allow the movement of fuel and air between the subsections in the tank, and the usage, number, diameter, and placement of these cutouts constitute the design parameters within the study. The qualitative diversity of these parameters is created by considering different values for each parameter. The name barrier is used for baffle structures that do not use cutouts, and in the situation where no barrier is used in the design, it is used on the first, third, and sixth ribs, as well as use on the second, fourth, and seventh ribs, are also considered. On the other hand, the diameters of the cutouts on these flanges are added to the designs with values ranging from 30 mm to 156 mm. In cutout placement, the centered cutout and 20 mm upward and downward placements are also considered. The use of single, twin, and triple cutouts on each baffle is also added to the study as another parameter. In addition, sloshing effects are examined by taking into account different fuel volume fractions, which are operational parameters, and these volume fractions are considered 30%, 45%, and 60%, which are the rates where the sloshing effect can be clearly observed. The study examines a flight maneuver known as bank-to-bank, in which the aircraft is tilted at a 45° angle for a duration of 10 seconds, serving as a measure of input acceleration. Additionally, the structural components that divide the wing tank into compartments and enhance structural integrity are regarded in this study as elements functioning as breakwaters. Their effectiveness in influencing the movement of fuel is analyzed. The thesis focuses on numerical modeling of fluid movements, utilizing numerical solver programs to conduct analyses. An analysis set is developed, comprising various combinations of design and operational parameters. Given the necessity for extensive calculations, one-dimensional analyses are initially performed under specific assumptions. The results are substantial, with all five input parameters interrelatedly influencing two output parameters. The complexity of this data network renders traditional analytical or numerical methods impractical for human examination. Consequently, big data analytics, aided by artificial intelligence, is employed to examine this complex data landscape. A DNN is constructed to further investigate the relationship between inputs and outputs, yielding quantitative insights into how inputs affect outputs. The data gathered indicates the dominance of input parameters expressed as a percentage. To investigate these parameters more thoroughly, three-dimensional CFD analyses are planned by selecting specific design combinations that exhibit a significant impact. CFD analyses have been performed by varying the relevant parameters while keeping others constant, allowing for comparative assessments. Following these studies, we have concluded by determining the sensitivity of one-dimensional analysis in relation to CFD, the accuracy of ANN calculations, and the effectiveness ranking of the parameters affecting fuel sloshing. The effects of fuel sloshing are examined not only from a theoretical standpoint but also in the context of specific maneuvers involving aircraft wing geometry. Additionally, the effectiveness of various design and operational parameters employed to mitigate these effects is demonstrated through real-world examples encountered in the aviation industry. Furthermore, the applicability of big data analytics processes in analyzing flow interactions with mechanical systems is validated using DNN, with results achieved at a level suitable for industry application.
Bir uçak kanat yakıt deposunda yakıt çalkantısının YSA ve HAD kullanılarak incelenmesi
Thesis (Ph.D.) -- Istanbul Technical University, Graduate School, 2025
Keywords: Flow analysis; Akış analizi; Computer aided simulation; Bilgisayar destekli benzetim; Computational fluid dynamics; Hesaplamalı akışkanlar dinamiği; Jet fuel; Jet yakıtı